An Overview of the Study of Language in the History of Philosophy (Ancient Greek to Medieval Age) - Parlindungan Pardede (Journal of English Teaching, 2022)
To English educators and researchers, having a good grasp of what a language is and how language learning takes place is important. To a certain extent, surveying the development of language studies is a good start to achieve the goal. This article is the first part of a literature review summarizing language studies taking place along the history of philosophy, starting from the ancient Greek to the postmodern era. This first part includes language studies conducted in the Ancient Greek Period up to the Medieval Age, whereas the second part will later discusses language studies carried out in the Renaissance Period, the Modern Period, and Post Modern Period. Data was gathered by surveying relevant and credible textbooks and scientific articles. The findings reveal that the initiators of the study of language issues were philosophers, not linguists. Philosophers in the Ancient Greek up to the Middle Ages had studied language as a topic of study because they need an effective language to assist them in studying philosophical ontologies and epistemology. This shows that humans never stop trying to understand language better as the need for language continuously changes to accommodate the development of human life and culture. The results of language studies in ancient Greece have provided us with various paradigms about the nature of language and micro-linguistic concepts in the form of elements of semantics, etymology, grammar, and various discourses that now become inherent parts of linguistic studies. Medieval philosophers focused on the use of straightforward, simple, and practical expressions as a language analytic method, etymological elements, and the development of Speculative Grammar.